2019
DOI: 10.1109/jlt.2019.2908447
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Core Microstructured Polymer Optical Fiber as Fiber-Enhanced Raman Spectroscopy Probe for Glucose Sensing

Abstract: This work reports the development and application of two liquid-core microstructured polymer optical fibers (LC-mPOF) with different microstructure sizes. They are used in a fiber-enhanced Raman spectroscopy sensing platform, with the aim of detecting glucose in aqueous solutions in the clinically relevant range for sodium-glucose cotransporter 2 inhibitor therapy. The sensing platform is tested for low-concentration glucose solutions using each LC-mPOF. Results confirm that a significant enhancement of the Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Recently, Azkune et al reported about a micro-structured polymer hollow-core optical fiber (POF) system ( Figure 9B) that was used for glucose sensing [102]. This FERS platform could perspectively be used for TDM of the sodium-glucose co-transporter 2 inhibitors in the therapy of diabetes mellitus.…”
Section: Fiber-enhanced Raman Spectroscopy For Drug Monitoringmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Azkune et al reported about a micro-structured polymer hollow-core optical fiber (POF) system ( Figure 9B) that was used for glucose sensing [102]. This FERS platform could perspectively be used for TDM of the sodium-glucose co-transporter 2 inhibitors in the therapy of diabetes mellitus.…”
Section: Fiber-enhanced Raman Spectroscopy For Drug Monitoringmentioning
confidence: 99%
“…This FERS platform could perspectively be used for TDM of the sodium-glucose co-transporter 2 inhibitors in the therapy of diabetes mellitus. Through careful preparation of the fiber and additional steps in data processing and analysis, glucose sensing in urine could be demonstrated via POF-FERS [102].…”
Section: Fiber-enhanced Raman Spectroscopy For Drug Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this problem polymer optical ber (POF), which has higher exibility, higher fracture toughness, and is more economical is employed for sensor fabrication. [16][17][18][19] Recently, nanocoating of ber probes because of the enhancement of sensitivity and improvement of the dynamic range, robustness and lifetime, has inspired a line of research in the eld of optical ber sensors. [20][21][22][23] These improvements are achieved because the nanostructure coating can provide additional mesoporosity, roughness, antibacterial behavior, localized surface plasmon resonances and quantum connement effects to the bare ber.…”
Section: Introductionmentioning
confidence: 99%